2019
DOI: 10.1002/smi.2858
|View full text |Cite
|
Sign up to set email alerts
|

What happens at home does not stay at home: The role of family and romantic partner conflict in destructive leadership

Abstract: Why leaders behave the way they do is of considerable importance. Our goal in this research was to understand how family‐to‐work conflict and romantic relationship conflict influence two different forms of destructive leadership, namely, abusive supervision and passive leadership. To do so, we invoke the conservation of resources theory. One hundred twenty‐three leader–follower dyads participated. Leaders completed questionnaires on their own family‐to‐work conflict and romantic relationship conflict, depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 96 publications
(158 reference statements)
0
20
0
Order By: Relevance
“…Furthermore, Tolman and Wang (2005) found that existing mental and physical health issues only partially explained victims working less hours. In a study focusing specifically on leaders, Dionisi and Barling (2019) found that depression mediated the effects of relationship conflict at home (which may be a potential indicator of WIPA) and abusive supervision at work, offering a unique perspective on how leaders' personal lives can influence their work behaviors. On the whole, the empirical findings on the mediating role of victims' mental health remains inconclusive and warrants further empirical investigation (Adams et al, 2013;Alexander, 2011;Carlson et al, 2002).…”
Section: Mediators Of Wipa and Work-related Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Tolman and Wang (2005) found that existing mental and physical health issues only partially explained victims working less hours. In a study focusing specifically on leaders, Dionisi and Barling (2019) found that depression mediated the effects of relationship conflict at home (which may be a potential indicator of WIPA) and abusive supervision at work, offering a unique perspective on how leaders' personal lives can influence their work behaviors. On the whole, the empirical findings on the mediating role of victims' mental health remains inconclusive and warrants further empirical investigation (Adams et al, 2013;Alexander, 2011;Carlson et al, 2002).…”
Section: Mediators Of Wipa and Work-related Outcomesmentioning
confidence: 99%
“…While majority of the studies were atheoretical, most of the studies that applied theories used mixed perspectives (k = 16) typically combining the feminist and resource perspectives (e.g., Lenze & Klasen, 2017;Sanders, 2015). This is closely followed by papers which used the feminist (k = 9; e.g., Naved et al, 2018;Tolman & Wang, 2005), resource (k = 9; e.g., Dionisi & Barling, 2019;Gibson-Davis et al, 2005), ecological (k = 6, e.g., Duffy, 2015;Slep et al, 2014), and social cognitive career perspectives (k = 5, e.g., Chronister et al, 2008;Davidson et al, 2012). Indeed, the use of theory in IPA and work research is still at a nascent stage.…”
Section: Mixed Perspectivesmentioning
confidence: 99%
“…As previously mentioned, both parent-child and romantic relationships are among the most salient of interpersonal relationships and have a strong influence on individual outcomes (e.g., Kim & Cicchetti, 2004;Marchand-Reilly, 2009). Both relationships influence various aspects of individuals lives, in both personal and professional ways (e.g., Dionisi & Barling, 2019;Finchman, 2003). For example, a study conducted by Dionisi and Barling (2019) examined the association between romantic relationship conflict and both abusive supervision and passive leadership and found that relational conflict was indirectly related to abusive supervision.…”
Section: Antecedents Of Motivation To Leadmentioning
confidence: 99%
“…Both relationships influence various aspects of individuals lives, in both personal and professional ways (e.g., Dionisi & Barling, 2019;Finchman, 2003). For example, a study conducted by Dionisi and Barling (2019) examined the association between romantic relationship conflict and both abusive supervision and passive leadership and found that relational conflict was indirectly related to abusive supervision.…”
Section: Antecedents Of Motivation To Leadmentioning
confidence: 99%
See 1 more Smart Citation